Kajian terhadap Peranan Kelompok Wanita Tani dalam Mendukung Desa Wisata Kecamatan Cangkringan Daerah Istimewa Yogyakarta - Pratama, Erik Andrian; Listiyani; Sayekti, Agatha Ayiek Sih (AGRIFITIA : Journal of Agribusiness Plantation, 2025)
This research was conducted in Cangkringan District, Sleman Regency. The aims of this research are (1) To find out the role of women farmer groups (KWT), in supporting tourist villages, (2) To find out the monthly income of KWT, (3) The obstacles faced by KWT in running a business. The research method uses qualitative and quantitative methods. Determining the sample using a census is an approach that requires every element of the population you wish to study to be included in the research, namely the total number of KWT members is 30 people. The results of this research show that the role of KWT Sarana Rejeki in supporting tourist villages includes managing agrotourism, providing facilities and promoting tourist villages, KWT Sarana Rejeki members earn an income of Rp. 500,000-1,000,000 for one month from the results of managing strawberry gardens and managing Klangon Hill tourism, the obstacles of KWT Sarana Rejeki are lack of wider market access, limited knowledge and skills in business management.